Bandagem elástica para osteoartrite de joelho: ensaio clínico randomizado - Pontin, José Carlos Baldocchi [UNIFESP] (2016)
Background: knee osteoarthritis (OA) is a degenerative chronic disease with a high prevalence worldwide and causes significant disability and is considered a public health problem. Evidence indicates that physical therapy provides satisfactory results in decreased pain and improved function of these patients. The elastic bandage is one of the modalities of physical therapy that has been used to treat various musculoskeletal injuries, but so far there is no consensus on its effectiveness in patients with knee osteoarthritis. Objectives: To investigate the efficacy of the additional use of elastic bandage to treatment based on kinesiotherapy to relieve pain and improve function in patients with knee osteoarthritis compared to patients who only underwent treatment based on kinesiotherapy. Methods: We randomized 82 patients with knee OA grade II according to the radiographic classification of Kellgren & Lawrence, and diagnosed based on the criteria adopted by the American College Rheumatology into two groups: intervention group (n = 41) in which it was carried out therapeutic exercise program based on stretching and strengthening associated with the application of elastic bandage and the control group (n = 41) who just held kinesiotherapy, without the addition of bandage. Data were analyzed according to the scale: NRS and WOMAC. Results: data were analyzed 80 patients. The group using the bandage showed a statistically significant reduction in pain compared to the pre-intervention moments and one month pre-intervention and end and from one month to the end of treatment. In the control group that underwent only the physiotherapy exercises there was a statistically significant decrease in pain between the pre-intervention moments and after a month of treatment, and between the pre-intervention and the end time point (after two months of intervention), but not there was a significant decrease in pain between the moments after one month and the end of treatment. After the intervention, the group that used the bandage showed statistically significant improvement compared to the control group indomain function and total WOMAC scale. Conclusion: The use of additional elastic bandage to treatment based on kinesiotherapy provided pain relief and improvement of function in patients with knee osteoarthritis compared to patients that underwent treatment based only on the kinesiotherapy.